2018
DOI: 10.1002/jmv.25265
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death‐1 3′‐untranslated region polymorphism is associated with spontaneous clearance of hepatitis B virus infection

Abstract: Hepatitis B virus (HBV)-specific CD8+ T cells play an important role in the clearance of HBV infection. Programmed cell death-1 (PD-1), an immunosuppressive molecule that regulates T-cell activation and peripheral immune tolerance, is increasingly shown to influence the outcome of HBV infection. rs10204525, a single-nucleotide polymorphism in the 3'-untranslated region (3'-UTR) of PD-1, has been associated with susceptibility and disease progression of chronic HBV infection in far-eastern patients. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Mediterranean HBV‐infected patients carrying GG and GA genotypes for PD1.6 displayed high PD‐1 mRNA expression. 27 Differently, a significant higher percentage of PD1 protein expression on T cells was observed for PD1.6 AA genotype as compared to GG genotype in the Chinese Han population. 28 Despite the discrepancy, regulation of PDCD1 gene expression by PD1.6 polymorphism is likely to happen.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Mediterranean HBV‐infected patients carrying GG and GA genotypes for PD1.6 displayed high PD‐1 mRNA expression. 27 Differently, a significant higher percentage of PD1 protein expression on T cells was observed for PD1.6 AA genotype as compared to GG genotype in the Chinese Han population. 28 Despite the discrepancy, regulation of PDCD1 gene expression by PD1.6 polymorphism is likely to happen.…”
Section: Discussionmentioning
confidence: 83%
“… 26 The AA genotype of PD1.6 was reported to be protective against HBV infection in Moroccan patients. 27 In contrast, the AA genotype of PD1.6 significantly increased the risk of persistent HCV infection in the Chinese Han population aged ≤56 years, while the G allele of PD1.6 was shown to clear HCV spontaneously and play protective roles in females infected with HCV. 28 To our knowledge, the present study is the first to reveal that the PDCD1 polymorphism is associated with the risk of psoriasis.…”
Section: Discussionmentioning
confidence: 97%
“…Polymorphisms in the PD-1 gene have been associated with an increased risk of various types of cancers and some of them alter protein expression and function [ 31 ]. The PD-1 rs10204525 C > T and rs7421861 A > G variants boost PD-1 expression and have been associated with increased risk of esophageal cancer in Asian individuals [ 32 ]. Furthermore, Kaplan-Meier survival curves showed that higher PD-1 gene expression contributed to worse survival of esophageal cancer patients [ 32 ].…”
Section: Dysregulation Of the Immune System In Human Nafldmentioning
confidence: 99%
“…Polymorphisms in the PDCD-1 gene have been associated with an increased risk of various types of cancers and some of them alter protein expression and function [ 55 ]. The PDCD-1 rs10204525 C > T is located in the 3′ UTR, it increases PD-1 expression and has been associated with persistence in HBV infection [ 57 ]. The rs7421861 A > G in PDCD-1 gene is localized in the intron 1, where there are several alternative splicing sites [ 24 ].…”
Section: Genetic Variants In Immunoregulatory Genes Modulate the Risk Of Hcc In Nafld Patientsmentioning
confidence: 99%